On the He-3 anomaly in hot subdwarf B stars - Schneider, David; Irrgang, Andreas; Heber, Ulrich; Nieva, M. F.; Przybilla, Norbert (SCIENDO, 2017)
Decades ago, He-3 isotope enrichment in helium-weak B-type main-sequence, in blue horizontal branch and in hot subdwarf B (sdB) stars, i.e., helium-core burning stars of the extreme horizontal branch, were discovered. Diffusion processes in the atmosphere of these stars lead to the observed abundance anomalies. Quantitative spectral analyses of high-resolution spectra to derive photospheric isotopic helium abundance ratios for known He-3 sdBs have not been performed yet. We present preliminary results of high-resolution and high S/N spectra to determine the He-3 and He-4 abundances of nine known He-3 sdBs. We used a hybrid local/non-local thermodynamic equilibrium (LTE/NLTE) approach for B-type stars investigating multiple He I lines, including lambda 4922 angstrom and lambda 6678 angstrom, which show the strongest isotopic shifts in the optical spectral range. We also report the discovery of four new He-3 sdBs from the ESO Supernova Progenitor survey. Most of the He-3 sdBs cluster in a narrow temperature strip between similar to 26000 K and similar to 30000 K and have almost no atmospheric He-4 at all. Interestingly, three He-3 sdBs show evidence for vertical helium stratification.
Keywords: Stars: chemically peculiar; Stars: atmospheres; Stars: fundamental parameters; Stars: abundances; subdwarfs; Stars: horizontal-branch